2016
DOI: 10.1136/neurintsurg-2016-012690
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the target puncture technique for treatment of osteoporotic vertebral compression fractures with intravertebral clefts

Abstract: Different puncture techniques were initially effective for all patients with IVCs. However, cement cleft filling by the traditional technique was found to have less stability causing higher VAS/ODI scores and greater loss of correction. Hence, our target puncture technique was recommended in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“… 21 Yu et al concluded that due to the presence of fibroperichondrium on the inner wall of the cleft and sclerosis of the surrounding bone, bone cement is difficult to diffuse into the surrounding cancellous bone and form effective adhesion, only form solid lump in the cleft. 22 The limited bone cement mass cannot be connected with the upper and lower adjacent endplates and cannot strengthen cancellous bone of vertebrae, which is more prone to stress shielding leading to recollapse, and cannot support the normal physiological stress from the body resulting in the continued existence of pain symptoms caused by osteoporosis. 23 Hence, bone cement injection should fill both the cleft in the vertebral body and the bone tissue around the cleft to increase the stability and prevent later loss of average vertebral height.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Yu et al concluded that due to the presence of fibroperichondrium on the inner wall of the cleft and sclerosis of the surrounding bone, bone cement is difficult to diffuse into the surrounding cancellous bone and form effective adhesion, only form solid lump in the cleft. 22 The limited bone cement mass cannot be connected with the upper and lower adjacent endplates and cannot strengthen cancellous bone of vertebrae, which is more prone to stress shielding leading to recollapse, and cannot support the normal physiological stress from the body resulting in the continued existence of pain symptoms caused by osteoporosis. 23 Hence, bone cement injection should fill both the cleft in the vertebral body and the bone tissue around the cleft to increase the stability and prevent later loss of average vertebral height.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the spongy distribution pattern should be formed during the injection of bone cement to obtain better therapeutic effect [21] . Yu et al concluded that due to the presence of broperichondrium on the inner wall of the cleft and sclerosis of the surrounding bone, bone cement is di cult to diffuse into the surrounding cancellous bone and form effective adhesion, only form solid lump in the cleft [22] . The limited bone cement mass cannot be connected with the upper and lower adjacent endplates and cannot strengthen cancellous bone of vertebrae, which is more prone to stress shielding leading to recollapse, and cannot support the normal physiological stress from the body resulting in the continued existence of pain symptoms caused by osteoporosis [23] .Hence, bone cement injection should ll both the cleft in the vertebral body and the bone tissue around the cleft to increase the stability and prevent later loss of average vertebral height.…”
Section: Discussionmentioning
confidence: 99%
“…A new pedicle entry point has been used for repeat puncture [9], but this is surgically time-consuming; also, sometimes, a new point cannot be chosen because, radiographically, the pedicle is obscured by the initially injected cement. Yu et al [2] used a puncture technique to treat clefted OVCFs. The needle tip was positioned in extra-cleft cancellous bone, and a balloon inflated to compact the surrounding bone until the periphery of the cleft was broken.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous vertebroplasty usually effectively treats osteoporotic vertebral compression fractures (OVCFs) with clefts [1,2]. However, recurrent back pain caused by re-fracture is not uncommon [3][4][5][6]; a cleft in the OVCF combined with poor cement dispersion within the fractured vertebra are the two prime risk factors [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation